Novel missense WFS1 variant causing autosomal dominant atypical Wolfram syndrome. (4th July 2022) - Mair, Hailey; Fowler, Nicholas; Papatzanaki, Maria E.; Sudhakar, Padmaja; Maldonado, Ramiro S.
ABSTRACT: Background: In contrast to the classic autosomal recessive Wolfram syndrome, Wolfram-like syndrome (WLS) is an autosomal dominant disease caused by heterozygous variants in the WFS1 gene. Here, we present deep phenotyping of a mother and son with a WFS1 variant NM_006005.3:c.2508 G > T, p. (Lys836Asn) detected with next-generation sequencing, which is novel at the nucleotide level. In this Greek family, the proband and mother had sensorineural hearing loss and mild non-progressive vision loss with optic nerve atrophy. An initial optic atrophy panel that did not test for WFS1 was unremarkable, but a broader inherited retinal dystrophy panel found the WFS1 variant. Conclusion: This study highlights the importance of including WFS1 sequencing in the evaluation of optic nerve atrophy to discover syndromic conditions.